Characterization and Suitability Assessment of Ameskroud Clay Deposits for Ceramic Applications - Aicha Idoum; Rachid Tiskatine; Soumia Mounir; Lahcen Bammou; Ahmed Aharoune (Advances in Materials Science and Engineering)
The identification of natural clay deposit parameters is critical for the development of ceramics. This research underscores the essential role of understanding clay properties in producing high-quality ceramics and represents a comprehensive characterization methodology, shedding light on the untapped potential of natural clay deposits for ceramic applications. This study investigates red clays from the Triassic, as well as yellow and gray clays from the Cretaceous period, collected from the western High Atlas of Morocco (Ameskroud). The characterization of clays from this geographic region is innovative, as they have not been previously investigated for their suitability within ceramic applications. The investigation encompasses an examination of the geological context, mineralogy, chemical composition, and physicochemical attributes of these clays. Furthermore, the thermal behavior, firing characteristics, and compressive strength of the clay samples were assessed when fired at 900°C, 1000°C, and 1100°C. Mineralogical analysis reveals that illite predominates with relatively low levels of kaolinite and chlorite. The primary chemical constituent is SiO2, followed by Al2O3 and Fe2O3. Notably, yellow clay exhibits a significant CaO content exceeding 10%. At 1100°C, the clay specimens exhibit reduced water absorption rates (ranging from 9.88% to 17.1%) and enhanced mechanical performance, with compressive strengths ranging from 22.33 MPa to 36.07 MPa, attributable to the sintering process. The findings affirm that the raw clays sourced from the Ameskroud region possess characteristics suitable for various ceramic applications, making them ideal candidates for the production of dense bricks and ceramic tiles.